2021
DOI: 10.1097/md.0000000000027661
|View full text |Cite
|
Sign up to set email alerts
|

Suprascapular nerve block and axillary nerve block versus interscalene nerve block for arthroscopic shoulder surgery

Abstract: Background:The interscalene brachial plexus block (ISB) is a commonly used nerve block technique for postoperative analgesia in patients undergoing shoulder arthroscopy surgery; however, it is associated with potentially serious complications. The use of suprascapular nerve block (SSNB) and axillary Nerve Block (ANB) has been reported as an alternative nerve block with fewer reported side effects for shoulder arthroscopy. This review aimed to compare the impact of SSNB and ANB with ISB during shoulder arthrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
1
8
0
5
Order By: Relevance
“…Moreover, SSNB does appear to reduce the risk of Horner syndrome, numbness, subjective dyspnea, and hoarseness [17]. Similar results in terms of analgesia and complications were found in another recent meta-analysis that compared the use of SSNB in combination with axillary nerve block (ANB) as an alternative to ISB during shoulder arthroscopy [18]. The supraclavicular block has also been successfully used for acute pain control following shoulder surgery as part of multimodal analgesia [19,20].…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, SSNB does appear to reduce the risk of Horner syndrome, numbness, subjective dyspnea, and hoarseness [17]. Similar results in terms of analgesia and complications were found in another recent meta-analysis that compared the use of SSNB in combination with axillary nerve block (ANB) as an alternative to ISB during shoulder arthroscopy [18]. The supraclavicular block has also been successfully used for acute pain control following shoulder surgery as part of multimodal analgesia [19,20].…”
Section: Discussionmentioning
confidence: 68%
“…Many previous studies have already described the combination of a suprascapular block with an axillary brachial plexus block. A recent meta‐analysis of those studies concluded that the combination of the two is an effective and safe alternative to the interscalene brachial plexus block for patients with pulmonary compromise [5]. When comparing the anterior suprascapular, interscalene and supraclavicular nerve blocks using 15 ml of 0.5% ropivacaine for major arthroscopic shoulder surgery, Auyong and colleagues demonstrated successful C5–8 dermatomal shoulder coverage at 60 min, following the anterior suprascapular nerve block, although this was less than the interscalene block [6].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the shoulder block may spare pulmonary function and diaphragmatic movement. Compared with ISBPB, suprascapular and axillary nerve blocks reduced the incidence of hemidiaphragmatic paresis and pulmonary dysfunction, while providing similar postoperative analgesia [32][33][34][35].…”
Section: Alternative Shoulder Blocks (Suprascapular Nerve Block or Ax...mentioning
confidence: 99%